2018
DOI: 10.3892/or.2018.6294
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta (YWHAZ) enhances tumorigenesis both in vivo and in vitro in bladder cancer

Abstract: Bladder cancer is the most common tumor of the urinary tract. Tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta (YWHAZ), a gene encoding the 14-3-3ζ protein, has been observed to be frequently amplified in bladder cancer. However, the role of 14-3-3ζ in various types of cancer is controversial. With reproduction of The Cancer Genome Atlas database, we searched the correlation of YWHAZ expression with survival outcomes of multiple cancers in silico. Our results revealed that only in bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…YWHAZ amplification is also reported to be clinically significant in other cancer types, including breast , prostate , lung , and oral cancers. Although YWHAZ has also been reported to act as a tumor suppressor during bladder cancer development , our results consistently show that YWHAZ overexpression negatively regulates apoptosis, enabling cellular adaptation to the presence of chemotherapeutic drugs. In contrast to anti‐apoptotic effects, other proteins participating in diverse functions/pathways within cells were found to be upregulated along with YWHAZ overexpression (see supplementary material, Tables S3 and S4).…”
Section: Discussionsupporting
confidence: 68%
“…YWHAZ amplification is also reported to be clinically significant in other cancer types, including breast , prostate , lung , and oral cancers. Although YWHAZ has also been reported to act as a tumor suppressor during bladder cancer development , our results consistently show that YWHAZ overexpression negatively regulates apoptosis, enabling cellular adaptation to the presence of chemotherapeutic drugs. In contrast to anti‐apoptotic effects, other proteins participating in diverse functions/pathways within cells were found to be upregulated along with YWHAZ overexpression (see supplementary material, Tables S3 and S4).…”
Section: Discussionsupporting
confidence: 68%
“…In addition, YWHAZ overexpression was also found to serve as a predictor for poor prognosis in ovarian cancer, 14 gastric cancer, 23 tongue squamous cell carcinoma, 25 prostate cancer, 26 and breast cancer. 29,30 However, no correlation between YWHAZ expression and prognosis was observed in bladder cancer patients 31 and hepatocellular carcinoma patients. 32 The above result showed that YWHAZ expression was associated with lymph node metastasis and present distant metastasis in NSCLC patients, and several published reports showed YWHAZ played important role in regulating tumor cell metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…One interesting thought could be that in TNBCs that overexpress PGRMC1, it could be enhancing the transcription of CCND1 even in tumors that lack ER and PR making it a potential target in TNBCs. The YWHAZ gene has been described in multiple cancers including non-small lung cancer ( 101 ), hepatocellular carcinoma ( 102 ), gastric cancer ( 103 ), bladder cancer ( 104 ), and in breast cancers ( 105 ). Overexpression of YWHAZ in breast cancers has been associated with chemoresistance to anthracyclines particularly associated with metastatic recurrence ( 105 ).…”
Section: Discussionmentioning
confidence: 99%